1997
DOI: 10.1002/cvde.19970030502
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐assisted CVD of cubic boron nitride

Abstract: Single-phase cubic boron nitride films of high quality might be of great importance as superhard wear-resistant coatings and semiconductive materials. This paper reviews deposition techniques, precursors, deposition parameters and substrates employed in plasma-assisted chemical vapor deposition (PACVD) of cubic boron nitride (c-BN) as well as procedures applied for the characterization of c-BN-containing films. Mechanisms of the formation of sp3-hybridized boron nitride during PACVD by use of either high-energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 110 publications
0
34
0
Order By: Relevance
“…[16] NH 3 and BBr 3 are two precursors that have previously been used for ALD and CVD of BN. [6,14] It is well known that photo-dissociation of NH 3 using an ArF excimer laser, which operates at 193 nm, produces NH and NH 2 . [17] Moreover, in the present study, BBr 3 was observed to dissociate when irradiated at this wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…[16] NH 3 and BBr 3 are two precursors that have previously been used for ALD and CVD of BN. [6,14] It is well known that photo-dissociation of NH 3 using an ArF excimer laser, which operates at 193 nm, produces NH and NH 2 . [17] Moreover, in the present study, BBr 3 was observed to dissociate when irradiated at this wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…For the deposition of the sp 3 -hybridized phases, highly energetic techniques such as RF and magnetron sputtering, ion-plating and ion-beam assisted deposition (IBAD) [4,5] or plasma enhanced chemical vapor deposition (PECVD) techniques such as electron cyclotron resonance PECVD or microwave PECVD [6] are commonly applied. These processes promote a bombardment of the growing film by atoms and/or ions, which is regarded as necessary, at least initially, to nucleate c-BN.…”
Section: Introductionmentioning
confidence: 99%
“…[133][134][135][136] For PECVD processes, Ge nanoparticles are produced through the reaction of GeCl 4 and H 2 . [123,124] The chloride/hydrogen/nitrogen systems have been proven to be effective for a number of nitride preparations, including BN, [137] TiN, [138,139] and FeN. [140] SiF 4 was also used in microcrystalline silicon thin-film deposition, which resulted in a better film quality compared to those deposited using SiH 4 .…”
mentioning
confidence: 98%